POLA KONSUMSI JAJANAN, SAYUR DAN BUAH PADA MAHASISWA PRODI GIZI STIKES SAMARINDA - Sapang, Ferliani Fransisca; Prihandani, Erlingga; Tuerah, Patrisia Maria Estefania; Salsabila, Nasywa Nida (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2025)
Students are a group in society that is particularly vulnerable to nutritional issues as they transition from late adolescence to early adulthood. They are also a group that quickly responds and adapts to lifestyle changes due to exposure to a more diverse environment. Unbalanced dietary patterns among students contribute to more complex nutritional problems. This study aims to explore the dietary consumption patterns of students in the nutrition program. The respondents in this study were all 32 students enrolled in the nutrition program at STIKES Samarinda. Data on dietary patterns were collected using a Food Frequency Questionnaire (FFQ), focusing on their eating habits over the past month. The dietary patterns of respondents in this study were assessed as unbalanced, characterized by more frequent consumption of snacks compared to infrequent intake of vegetables and fruits. This imbalanced dietary habit may lead to weight gain that triggers obesity, which over the long term could increase the risk of developing metabolic syndrome.